Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.1002/jsfa.6720
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of extraction conditions and fatty acid characterization of Lactobacillus pentosus cell‐bound biosurfactant/bioemulsifier

Abstract: The optimum extraction conditions of biosurfactant were achieved at 45 °C at 120 min and using 9 g kg(-1) of salt. In all the assays biosurfactant from L. pentosus yielded more stable emulsions and higher emulsion volumes than polysorbate 20.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
49
0
4

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 81 publications
(59 citation statements)
references
References 26 publications
6
49
0
4
Order By: Relevance
“…In fact, we found only one study dedicated to the use of statistical design for the improvement of Bs recovery [48]. They optimized the extraction conditions of a Lactobacillus pentosus cell bound biosurfactant/emulsifier using a Box-Behnken response surface methodology.…”
Section: Improving Downstream Processesmentioning
confidence: 99%
“…In fact, we found only one study dedicated to the use of statistical design for the improvement of Bs recovery [48]. They optimized the extraction conditions of a Lactobacillus pentosus cell bound biosurfactant/emulsifier using a Box-Behnken response surface methodology.…”
Section: Improving Downstream Processesmentioning
confidence: 99%
“…Moreover, C16:0 and C18:0 were the most abundant fatty acids in the biosurfactant produced by Lactococcus sp. (Saravanakumari and Mani, 2010; Vecino et al, 2014). Many earlier reports demonstrated that the biochemical composition of biosurfactant produced by Bacillus genus varied according to the species.…”
Section: Discussionmentioning
confidence: 99%
“…Advances in biotechnological research have led to the discovery of novel active ingredients, consolidating the development of a new class of products known as biocosmetics . Biosurfactants can play a role in these products, as their surface properties and biological activities make these natural compounds adequate for use in cosmetic applications . Glycolipids (sophorolipids, rhamnolipids, and MELs) and lipopetides (surfactin) are the most widely used biosurfactants in cosmetics due to their multifunctional profile …”
Section: Biosurfactants In the Cosmetic Industrymentioning
confidence: 99%
“…39 Biosurfactants can play a role in these products, as their surface properties and biological activities make these natural compounds adequate for use in cosmetic applications. 40 Glycolipids (sophorolipids, rhamnolipids, and MELs) and lipopetides (surfactin) are the most widely used biosurfactants in cosmetics due to their multifunctional profile. 11 Microemulsions formed by biosurfactants can be used to provide functional components and antioxidants to cosmetics.…”
Section: Natural Products In the Cosmetic Industrymentioning
confidence: 99%
See 1 more Smart Citation